Composite risk index for designing smart climate and energy policies - Kristiāna Dolge; Dagnija Blumberga (Environmental and Sustainability Indicators, 2021)
This study presents an innovative model for a comprehensive, in-depth risk assessment of climate and energy policies. A risk matrix framework combined with a composite index methodology is applied to produce a risk index composed of 24 risk indicators grouped into six main risk categories - political, technical, economic, environmental, social and administrative. The model was applied to assess five different climate policy instruments, using both an ex-post and ex-ante assessment. The results highlight the critical risk factors for each policy instrument and identify existing policy vulnerabilities that require immediate mitigation action. The model could be used for decision-making at all levels of government and serve as a valuable tool for designing sustainable and successful environmental policies.